DIGITAL LITERACY CULTURE IN MILENIAL STUDENTS AT BOARDING SCHOOLS - Al Anshori, Habib Anwar; Baharun, Hasan; Hamada, Salwa Elsayed; Hasanah, Nasihatun (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2022)
This study aims to analyze the introduction of literacy culture to millennial students in Islamic boarding schools. The research method used is a qualitative case study type. In order to get an overview of the literacy culture of millennial students at Islamic boarding schools, the researchers made direct observations and documented learning activities at the Islamic boarding schools. Interviews were conducted with boarding school caretakers, foundation heads, asatidz and administrators in their respective areas. Qualitative analysis activities consist of three strands, namely data reduction, data presentation, and drawing conclusions or verification. The results showed that the strategy for introducing literacy culture to millennial students at Islamic boarding schools was carried out through learning analysis, learning system design and evaluation. This research has implications that a boarding school or institution that has innovation combined with the creativity of its asatid in managing knowledge (literacy culture) will be able to arouse the motivation and intelligence of students in totality.